Proposal AHP method for Increasing the Security Level in the Railway Station - Szatmári, Michal (Transportation research procedia (Online), 2021)
Railway stations are objects that have a social significance because they provide services to customers and passengers of rail transport. There is a high frequency of movement of people in their premises and their near surroundings, but at the same time, it is true that these objects are characterized by a high level of vulnerability. In order to increase the level of vulnerability and safety, measures are usually taken in the form of regulations, rules on behavior in the building, movement in the building, prohibitions in the building, etc., but also the security elements that make up the protection system are used. How the security elements will be deployed and used must be thought and designed and only then decided on their application. It is the process of selection and application of security elements, which is the task of the subject decision-making that must be considered according to specific criteria, which will compare the individual possibilities or variants of using the elements. The decision-making process according to several criteria and variants is called multi-criteria decision-making. One of the methods used to calculate the optimal or most suitable variant for a railway station is the AHP method (analytical hierarchical process. In the article, the author describes the theoretical apparatus of multi-criteria decision making and the AHP method, which he applies in a case study to a specific object.